Taichi on the brain: an activation likelihood estimated meta-analysis of functional neuroimaging data - Wang, Shengxin; Liu, Tianyu; Du, Jingtao; Chen, Jun; Luo, Xiufen; Meng, Yujie; Zeng, Chun; Zhang, Xupeng; Shao, Binghua (Frontiers in Human Neuroscience, 2025)
IntroductionTai Chi Chuan (TCC) is an exercise regimen renowned for its comprehensive benefits to both physical and mental health. The present research endeavor aims to elucidate the neurocognitive impacts of TCC compared to alternative exercise modalities or therapeutic interventions.MethodsA systematic meta-analysis was undertaken, encompassing a rigorous review of diverse datasets, wherein 422 scholarly articles were examined, with a subset of 18 articles meeting the stringent criteria for inclusion in the analytical framework.ResultsThe study cohort comprised 677 participants, characterized by a mean age of 56.52 ± 14.89 years and an average educational attainment of 11.06 ± 3.32 years. Noteworthy alterations in functional neural activity were identified within the superior frontal gyrus.DiscussionThis comprehensive analysis provides significant insights into the enduring neural modifications and the distinctive contributions of TCC to cognitive health. Nevertheless, it is imperative to acknowledge the potential for bias in smaller functional magnetic resonance imaging studies owing to their inconclusive outcomes. This observation underscores the critical need for collaborative, multicenter research initiatives with expanded sample sizes to enhance the robustness and generalizability of future findings.